ECOLOGICAL QUALITY AND ECOSYSTEM SERVICES IN THE JORDÁN-CHICAMOCHA RIVER (Boletín de la Sociedad Zoológica del Uruguay, 2024)
The Jordán-Chicamocha River, born in the Runta district south of Tunja, has undergone significant changes due to human development, which has led to eutrophication, loss of vegetation cover, and increased frequency of flooding. The ecological quality and ecosystem services (ES) were evaluated in three sections of the river through in situ sampling of physicochemical variables and analysis of benthic macroinvertebrates, identifying 13 families, with a predominance of Tubificidae and Glossiphoniidae. These findings are related to high levels of hardness, phosphates, nitrates and electrical conductivity, in addition to evidence of physical degradation in the riverbed and riverbank. According to the Andean Biological Index (ABI), the ecological quality is classified as moderate, very poor, and poor. A total of 100 surveys indicated that, despite the provision of wildlife habitats and water availability, these benefits diminish with increased urbanization and lower ecological quality. Anthropogenic activities exert pressure on the ecosystem, altering the composition and distribution of the evaluated community and affecting the ecological quality, functions and services of the aquatic ecosystem.
Keywords: Macroinvertebrates; pollution; physical degradation; urbanization